Combinação terapêutica da proteína McLTP1 e oxaliplatina na atividade antitumoral e na neuropatia sensitiva periferica em modelo de câncer de colorretal - Abucater, Breno Leonardo da Silva Mansur (2025)
Oxaliplatin (OXL) is 3rd generation platinum based antineoplastic drug, used as the 1st line of treatment for colorectal cancer (2nd place in incidence in Brazil), of extreme importance oncology, whose main effect is collateral peripheral sensory neuropathy (PNS), a debilitating and painful neurotoxic condition that can lead to treatment suspension or dose reduction, therefore decreasing CRC patient survival. Studies demonstrate that a protein purified from the seed of Morinda citrifolia (McLTP1) has analgesic and anti-inflammatory properties and prevented OXL-induced NSP in Swiss mice. There is still no validated therapy for the prevention or treatment of NSP by OXL and it is of interest that therapeutic proposals have an anti-neuropathic effect and at the same time do not reduce the antitumor effect of the antineoplastic drug. Thus, the objective of this work was evaluate the effect of McLTP1 on the antitumor activity of oxaliplatin and on the associated NSP in animals with murine colorectal adenocarcinoma cell tumor CT26.WT. For this, male BALB/c mice (20 to 25g), from the NPDM-UFC animal facility, were inoculated subcutaneously in the flank with the CT26.WT cells (0.25 x105 cells/animal). 10 days after inoculation, the animals were divided into 4 groups: control (treated with the OXL vehicle), group treated with McLTP1 (4mg/kg; p.o; daily), OXL group (6 mg/kg.iv; every 48 hours) and group McLTP1 +OXL. Tumor growth was monitored daily until the 14th day. NSP was assessed by mechanical and thermal allodynia tests. At the end of the experiment, the mice were euthanized, peripheral blood was collected for leukometry and the tumor was collected for wet weight assessment and immunofluorescence assay for Ki67, CD31 and HMGB1. Additionally, the in vitro cytotoxicity of McLTP1 alone and in combination with OXL was assessed by the MTT colorimetric assay. The CT26.WT cells were exposed to increasing concentrations of McLTP1 (0.024 to 200 μM) for 48 to 72 hours. After determining the IC50 of McLTP1, a curve was performed for OXL alone (0.39 μM to 20 μM) and another curve in association with McLTP1 at a fixed concentration (IC50). The results showed that treatment with McLTP1 inhibited the development of NSP caused by OXL, reducing mechanical allodynia by up to 96.8% (p<0.001) and cold allodynia by 85.2% (p<0.001). In evaluating the antitumor effect, McLTP1 and OXL decreased tumor size by 51.1% and 81.3% (p<0.001), respectively, and tumor weight by 76.1% (p<0.05). The association of McLTP1+OXL reduced tumor size and weight by 63% and 78% (p<0.001). There was no difference between the group treated with OXL and the group treated with the combination (OXL+ McLTP1). All treatments inhibited tumoral labeling for Ki67 and CD31. HMGB1 labbeling was increased in all treated groups. McLTP1 increased the effect of OXL on this marker. OXL decreased the total number of leukocytes, especially lymphocytes (89.5%) when compared to the control (p<0.05). This effect was prevented by McLTP1 in 78.8% (p<0.01). In vitro, OXL decreased cell viability with IC50 of 1.74, 2.6 and 0.75μM after 48, 72 and 96h of incubation. McLTP1 presented an IC50 of 104.7, 44.12 and 23.6μM in the same period. The association of McLTP1 with OXL lowered the IC50 to 1.35 and 0.24 μM at 72 and 96 h (p<0.05), demonstrating a potentiating effect. The results are promising considering the potential of McLTP1 as an adjuvant in colorectal cancer therapy with OXL for both its neuroprotective and antitumor effects.